Extracorporeal membrane oxygenation for COVID-19: evolving outcomes from the international Extracorporeal Life Support Organization Registry. Issue 10307 (2nd October 2021) - Barbaro, Ryan P; MacLaren, Graeme; Boonstra, Philip S; Combes, Alain; Agerstrand, Cara; Annich, Gail; Diaz, Rodrigo; Fan, Eddy; Hryniewicz, Katarzyna; Lorusso, Roberto; Paden, Matthew L; Stead, Christine M; et al.
Summary: Background: Over the course of the COVID-19 pandemic, the care of patients with COVID-19 has changed and the use of extracorporeal membrane oxygenation (ECMO) has increased. We aimed to examine patient selection, treatments, outcomes, and ECMO centre characteristics over the course of the pandemic to date. Methods: We retrospectively analysed the Extracorporeal Life Support Organization Registry and COVID-19 Addendum to compare three groups of ECMO-supported patients with COVID-19 (aged ≥16 years). At early-adopting centres—ie, those using ECMO support for COVID-19 throughout 2020—we compared patients who started ECMO on or before May 1, 2020 (group A1), and between May 2 and Dec 31, 2020 (group A2). Late-adopting centres were those that provided ECMO for COVID-19 only after May 1, 2020 (group B). The primary outcome was in-hospital mortality in a time-to-event analysis assessed 90 days after ECMO initiation. A Cox proportional hazards model was fit to compare the patient and centre-level adjusted relative risk of mortality among the groups. Findings: In 2020, 4812 patients with COVID-19 received ECMO across 349 centres within 41 countries. For early-adopting centres, the cumulative incidence of in-hospital mortality 90 days after ECMO initiation was 36·9% (95% CI 34·1–39·7) in patients who started ECMO on or before May 1 (group A1) versus 51·9% (50·0–53·8) after May 1 (group A2); at late-adopting centres (group B), it was 58·9% (55·4–62·3). Relative to patients in group A2, group A1 patients had a lower adjusted relative risk of in-hospital mortality 90 days after ECMO (hazard ratio 0·82 [0·70−0·96]), whereas group B patients had a higher adjusted relative risk (1·42 [1·17−1·73]). Interpretation: Mortality after ECMO for patients with COVID-19 worsened during 2020. These findings inform the role of ECMO in COVID-19 for patients, clinicians, and policy makers. Funding: None.